Factors associated with poor functional outcome in bipolar disorder: sociodemographic, clinical, and neurocognitive variables. (3rd May 2018) - Sanchez‐Moreno, J.; Bonnin, C. M.; González‐Pinto, A.; Amann, B. L.; Solé, B.; Balanzá‐Martinez, V.; Arango, C.; Jiménez, E.; Tabarés‐Seisdedos, R.; Garcia‐Portilla, M. P.; Ibáñez, A.; Crespo, J. M.; et al.
Abstract : Objective: The current investigation aimed at studying the sociodemographic, clinical, and neuropsychological variables related to functional outcome in a sample of euthymic patients with bipolar disorder(BD) presenting moderate‐severe levels of functional impairment. Methods: Two‐hundred and thirty‐nine participants with BD disorders and with Functioning Assessment Short Test(FAST) scores equal or above 18 were administered a clinical and diagnostic interview, and the administration of mood measure scales and a comprehensive neuropsychological battery. Analyses involved preliminary Pearson bivariate correlations to identify sociodemographic and clinical variables associated with the FAST total score. Regarding neuropsychological variables, a principal component analysis (PCA) was performed to group the variables in orthogonal factors. Finally, a hierarchical multiple regression was run. Results: The best fitting model for the variables associated with functioning was a linear combination of gender, age, estimated IQ, Hamilton Depression Rating Scale (HAM‐D), number of previous manic episodes, Factor 1 and Factor 2 extracted from the PCA. The model, including all these previous variables, explained up to 29.4% of the observed variance. Conclusions: Male gender, older age, lower premorbid IQ, subdepressive symptoms, higher number of manic episodes, and lower performance in verbal memory, working memory, verbal fluency, and processing speed were associated with lower functioning in patients with BD.